Breast screening and health issues among rural females in malaysia: how much do they know and practice? - Dahlui, M.; Gan, D.E.H.; Taib, N.A.; Lim, J.N.W. (2012)
OBJECTIVE: This study investigated rural women's knowledge of breast cancer and screening methods by ethnicity and examined the predictors of breast screening methods. METHODS: A cross-sectional survey was conducted in 2011 in five rural districts of Perak; 959 women were interviewed using a semi-structured questionnaire. ANOVA and regression analysis were used in data analysis. RESULTS: Women below 50years old, of Malay ethnicity and who had secondary education scored better than those older, of Chinese ethnicity and had primary education (p<0.001). The uptake of breast self-examination (BSE), clinical breast examination (CBE) and mammogram was 59, 51 and 6.8, respectively. Multivariate analysis revealed knowledge of breast cancer and CBE as top predictors of BSE, being married and knowledge of breast cancer as top predictors for CBE; and CBE as the top predictor of mammography uptake. Support from husbands and family members for breast cancer screening was a predictor for CBE and BSE. CONCLUSION: Knowledge of breast cancer and its screening uptake varies by ethnicity, location and the type of support received. Efforts and approaches to improve the women's knowledge of breast cancer and its screening uptake therefore should be customized to address the different influencing factors.